Demanding Equal Inheritance Rights For Women: Tension Among Shari’a and Tunisia’s New Constitution 2014 - Budi Juliandi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
President  Essebsi  (2017) approved  the  law of gender  equality  in  inheritance  in Tunisia. Instead of gaining public appreciation of Islam, this achievement was seen as contrary to sharia. This research seeks to address whether or not there could be a common ground between  applying  sharia and gender equality through an examination of sharia regarding  inheritance, and, finally, an attempt to show the relationship between sharia and the  Tunisia’s constitution of 2014 in responding to social change. The paper argues that in spite of the constitution’s progressive language, women still face legal discrimination in  their ability  to inherit because of sharia.